Design of a novel energy harvesting mechanism for underwater gliders using thermal buoyancy engines. (15th June 2023) - Hou, Hongbo; Arredondo Galeana, Abel; Song, Yang; Xu, Gang; Xu, Yunxin; Shi, Weichao
Abstract: Underwater gliders (UGs) are becoming popular in ocean exploration. However, the main limitation for their development is their supply of energy. This paper proposes a novel energy harvesting mechanism for an underwater glider equipped with a thermal buoyancy engine. The thermal buoyancy engine changes the buoyancy of the glider, due to the difference of temperature of the ocean, and it drives the glider up and down in the water. These manoeuvres drive a turbine behind to harvest energy. Based on this harvesting mechanism, first, a new type of thermal buoyancy engine with high ballast capacity is presented. Secondly, a dedicated turbine, mounted behind the glider, is optimally designed based on the Blade Element Momentum Theory (BEMT). In order to consider the un-uniform inflow generated by the wake of the glider, an upgraded version of the BEMT model has been developed. With the results obtained in this paper, enhanced energy efficiency for a self-sustainable underwater glider can be achievable. Highlights: A new-type energy harvesting mechanism applied on underwater glider. A new-type thermal buoyancy engine in the energy harvesting mechanism. A math model for optimizing the turbine in the energy harvesting mechanism. The energy harvesting energy has potential to allow underwater glider to be self-sustainable.